2006
DOI: 10.1590/s0100-46702006000200009
|View full text |Cite
|
Sign up to set email alerts
|

Prochloraz residue levels in ginger submitted to Sportak 450 CE" postharvest treatment

Abstract: A preliminary study was conducted to determine the residue levels of prochloraz in ginger samples treated with Sportak 450 CE  (prochloraz as active ingredient) under laboratory conditions and cold-storage for 15 days at 10°C and 89% RH. Sampling was carried out at 10 and 15 days after Sportak 450 CE  dip treatment (450 and 900 µg mL -1 ). Pesticide residues were determined by GC-ECD. During the study, residue levels in ginger ranged between 3.6 and 10.6 mg Kg -1 for prochloraz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Most of them were on vegetable, fruit, and cereals [2][3][4][5][6][7][8][9][10][11][12][13][14][15], some is on soil and water [16,17]. It is not found on herbal medicines.…”
Section: Introductionmentioning
confidence: 99%
“…Most of them were on vegetable, fruit, and cereals [2][3][4][5][6][7][8][9][10][11][12][13][14][15], some is on soil and water [16,17]. It is not found on herbal medicines.…”
Section: Introductionmentioning
confidence: 99%
“…33 De Paoli et al (1997) used the GC-ECD method for determination of prochloraz in the form of 2,4,6-trichlorophenol in vegetables, fruits and wheats and found that the LOD ranged from 10 to 500 mg kg À1 and recovery was in the region of 72-102%. 36 When compared to the methods used in the studies mentioned above, the method used in this study was more sensitive than those used in the studies mentioned above in terms of the LOD and LOQ levels. 34 They found that LOQs were 100 mg kg À1 (LC-MS) and 500 mg kg À1 (LC-UV).…”
Section: Resultsmentioning
confidence: 86%
“…(2006) determined the prochloraz residue levels in ginger, as 2,3,4-trichlorophenol, and they found that LOD and LOQ using the GC-ECD method were 100 and 200 mg kg À1 , respectively. 36 When compared to the methods used in the studies mentioned above, the method used in this study was more sensitive than those used in the studies mentioned above in terms of the LOD and LOQ levels.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation